Phylogeny and divergence times of the Coluteoid clade with special reference to Colutea (Fabaceae) inferred from nrDNA ITS and two cpDNAs, matK and rpl32-trnL(UAG) sequences data. (2nd November 2017) - Moghaddam, M.; Kazempour Osaloo, S.; Hosseiny, H.; Azimi, F.
Abstract: This study reconstructed the phylogeny of the Coluteoid clade using nrDNA ITS and plastid mat K and rpl 32- trn L(UAG) sequences data. The analyses resolve a well-supported Coluteoid clade, as sister to Astragalus s.str. + Oxytropis, nested within the larger, strongly supported Astragalean clade. The Coluteoid clade is now composed of 12 genera including Podlechiella, Swainsona, Carmichaelia, Clianthus, Montigena, Phyllolobium, Lessertia, Sutherlandia, Sphaerophysa, Smirnowia, Eremosparton and Colutea. Within this clade, Podlechiella is the first diverging lineage followed by successive subclades of Carmichaelia + Clianthus + Swainsona, Phyllolobium, Lessertia + Sutherlandia, Sphaerophysa + Smirnowia + Eremosparton, and Colutea. We assigned the formal tribal name to this clade and redefined the tribe Coluteae. A diagnostic key to the genera of the tribe is presented. Astragalus cysticalyx and A. sinicus have no relationship with the Coluteoid clade, instead, they are nested in Astragalus s. str. Resolution within Colutea is rather low, but several smaller subclades with low to high supports are found in the genus. None of the large sections in Colutea are monophyletic. Divergence time estimates revealed that the Coluteoid clade originated in the Early Miocene (20.4 Mya). Most of its members were diverged during the Late Miocene to Pliocene. Colutea and Podlechiella form the youngest lineages where the diversification occurred in the Pliocene-Pleistocene.